ChemInform Abstract: The Role of Naked Fluoride Ion as Base or Catalyst in Organic Synthesis. Issue 33 (July 2016) - Hameed, Abdul; Alharthy, Rima D.; Iqbal, Jamshed; Langer, Peter
Abstract: Review: 163 refs.